Hubungan Antara Stres Psikologis Dan Olahraga Terhadap Terjadinya Dismenore Primer Pada Mahasiswi Fakultas Kedokteran Universitas Sebelas Maret - Mutiara Rizky Ananda; Eric Edwin Y; Lilik Wijayanti (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: Prevalence of primary dysmenorrhea in the adolescent in Surakarta is 87,7% and 15% of women in Indonesia complained that their activity were interrupted due to dysmenorrhea. Psychological stress and irregular sports allegedly have connection in increase the incidence of primary dysmenorrhea. This research aims to know the relation between psychological stress and exercise against the occurrence of primary dysmenorrhea. Methods: This study is analytical observational with cross sectional approach, and using primary data. This study using medical student of 2010, 2011, 2012 at Sebelas Maret University as sample, taken by simple random sampling methods about 62 samples. Data analysis using Chi Square test and binary logistic regression. Results: Result of data analysis using Chi Square test shows p value for the relationship of psychological stress with primary dysmenorrhea is 0,013 whereas p value of relations sports with primary dysmenorrhea is 0,009. For the results of the analysis data using binary logistic regression found that psychological stress has OR = 0,352 whereas exercise has OR = 3,808. Conclusions: Based on result of the study can be concluded that there is a relationship between psychological stress and exercise against the occurrence of primary dysmenorrhea in the medical student of Sebelas Maret University Surakarta. Keywords: Psychological Stress, Exercise, Primary Dysmenorrhea.